Performance of a test embankment on very soft clayey soil improved with drain-to-drain vacuum preloading technology. Issue 5 (October 2019) - López-Acosta, N.P.; Espinosa-Santiago, A.L.; Pineda-Núñez, V.M.; Ossa, A.; Mendoza, M.J.; Ovando-Shelley, E.; Botero, E.
Abstract: Vacuum consolidation of soils is a technology that, to date, has not been implemented in the Valley of Mexico, where clays are highly compressible and have very low shear resistance and low permeability. This paper describes the experience of a test embankment, in which the drain-to-drain vacuum preloading was assessed. The evaluation includes the description of the subsoil conditions, characteristics of the embankment, construction process and instrumentation that was installed. The test lasted approximately one year with a vacuum applied for six months. The monitoring results showed that the vacuum distributed along the vertical drains and on the surface soil layers accelerated the consolidation, reduced the lateral displacements toward the outside of the platform and increased the effective stress of the soil to a depth similar to the length of the drains. However, there were vacuum pressure losses of approximately 30% between the pumps and end of the horizontal flexible pipes that distribute the vacuum. These losses of vacuum pressure affected the soil consolidation process.